QMTool an XML-based management platform for QoS-aware IP networks. - Dimopoulou, L. (IEEE Network : the magazine of global information exchange)
Technological and human factors have contributed to the increasing complexity of the network management problem. Heterogeneity and globalization of network resources have, on one hand, increased user expectations for flexible and easy-to-use environments and, on the other, propounded entirely novel ways to face the management problem. Several research efforts recognize the need for integrated solutions to manage both network resources and services in open and global environments. Undoubtedly, these solutions should permit the coexistence of different management models and should interoperate with legacy systems. The presented management system, QoS management tool (QMTool), aspires to address the heterogeneity, complexity, and dynamic behavior of QoS-enabled IP networks by taking advantage of the optimum fit of a number of novel technologies. A layered framework architecture, including element, network management, and visualization service, is provided, and a high level of information abstraction in network configuration and monitoring is introduced mainly based on the capabilities of the Extensible Markup Language (XML). Moreover, the functional components for providing (re-)configuration, fault management monitoring, and network visualization facilities are also presented, followed by notes of implementation issues.